Effect of temperature on population growth of copepod, Euterpina acutifrons - Marlena Amatus; Najamuddin Abdul Basri; Rossita Shapawi; Sitti Raehanah Muhamad Shaleh (Universiti Malaysia Sabah, 2020)
This study was aimed at determining the optimum temperature for culturing the copepod, Euterpina acutifrons. The trial was conducted for 10 days in chambers at temperatures of 25⁰C, 27⁰C, 29⁰C and 31⁰C. Ten adult individuals of the copepod were randomly collected and placed into three replicate experimental flasks for each treatment. Throughout the trial, the salinity, light intensity, and photoperiod were maintained at 30 ±2psu, 100molm-2s-1 and 12:12 light-dark cycle, respectively. The copepods were fed with 80,000cell/ml Isochrysis sp. daily. At the end of the trial, the total numbers of E. acutifrons nauplii, copepodites and adults were determined and counted using Sedgwick-Rafter. The highest population was found at 27⁰C with mean total population of 800±100 individuals from an initial of 10 individuals. This was followed by those reared at 25⁰C and 29⁰C where the population counts were 700±100 individuals and 367±115 individuals, respectively. At the 31⁰C, all the copepod specimens were found dead on day 5th. Statistical analysis showed that the temperature had a significant effect (P<0.05) on the population growth of the copepod. The population of nauplii was higher in lower temperature (25⁰C) set compared to the one at higher temperature (29⁰C). However, the copepodite number was greater at 27⁰C. Growth of the copepod was highest at 27⁰C (0.438K) followed by sets at 25⁰C (0.425K) and 29⁰C (0.361K). Based on the results of this analysis, it is suggested to culture copepod at temperature 25⁰C for nauplii production and 27⁰C for producing more copepodites.